Development of Learning Media Maritime English Textbook for Ratings Forming - Mashartanto, Achmad Ali; Pranata, Wibisana; Siska, Syafni Yelvi (Universitas Pendidikan Mandalika, 2024)
Maritime English is stated as one of General Courses at Merchant Marine Polytechnic of West Sumatera. Based on the initial observation, there still some problems found related to Maritime English learning. This research conducted due to several problems, namely the low level of cadets’ Maritime English language skills, limited Maritime English learning media and the absence of Specific Maritime English textbook. This research aims to produce validity, practicality and effectiveness of learning media Maritime English for Ratings Forming textbook. This research is Research and Development (R&D) using the 4-D (four D) model. This research was conducted at Merchant Marine Polytechnic of West Sumatera. The subject of this research was the cadets of the nautical class. Validity test data is obtained from validation sheets for aspects of material/content, appearance/design and language. Practicality test data was obtained through questionnaire responses from cadets and lecturers. The effectiveness data was obtained from the cadets’ assessment results of Maritime English language skills. The research results show that the validity of material/content, appearance/design and language of the textbook is in the very valid category. The practicality of the textbook is very practical. Then, the effectiveness of Maritime English for Ratings Forming textbook is found effective. It can be concluded that the Maritime English for Ratings Forming textbook can improve the Maritime English language skills of cadets at Merchant Marine Polytechnic of West Sumatera. This research can provide several implications for the cadets, lecturers and institution. Maritime English Textbook for Ratings Forming can be used as learning media for the cadets and teaching media for the lecturers.